Some Aspects of Liver Function Status in G6PD Deficient Neonates and Its Relationship with G6PD - Akhter, Nilufa; Begum, Noorzahan; Ferdousi, Sultana (Journal of Bangladesh Society of Physiologist, 2012)
Background: Neonatal jaundice is a common cause of newborn hospital admission. G6PD enzyme defects is one of the factor to develop neonatal hyperbilirubinemia, which may be related to abnormal liver function in this group of neonates. Objective: To observe some aspects of liver function status by measuring serum bilirubin and alanine amino transferase levels in G6PD deficient neonates and also their relationship with erythrocyte G6PD levels. Methods: The study was conducted on 30 male, term neonates with G6PD deficiency in the Department of Physiology, Bangabandhu Sheikh Mujib Medical University (BSMMU) between 1st July 2007 to 30th June 2008. For comparison age and sex matched 30 apparently healthy neonates without deficiency (control group) were also included in the study. Erythrocyte G6PD level was measured by Spectrophotometric method by using kit of Randox. Alanine amino transferase level was done by Schumann and Klauke method. For statistical analysis independent sample t test and Pearsons correlation coefficient test were performed as applicable by using SPSS for windows version-13 Results: In this study, significantly (p<0.001)higher level of serum bilirubin & ALT were found in G6PD deficient group in comparison to those of non-deficient group. Further more, serum bilirubin & ALT levels were negatively (r=-.671, (r= -.534) correlated with erythrocyte G6PD level and it was statistically significant (p<0.01) in G6PD deficient group. Again, significant (p<0.05) positive (r=+.429) correlation of serum bilirubin level was observed in non deficient group. Whereas, non significant positive (r=+.041) correlations of ALT was found in non deficient group. Conclusion: From the study results it can be concluded that higher level of alanine amino transferaseand hyperbilirubinemia were present in G6PD deficient neonates & increase serum bilirubin and serum alanine amino transferase levels were associated with degree of G6PD enzyme deficiency. DOI: http://dx.doi.org/10.3329/jbsp.v7i1.11158 J Bangladesh Soc Physiol. 2012, June; 7(1): 36-40